Potent bicyclic inhibitors of malarial cGMP-dependent protein kinase: approaches to combining improvements in cell potency, selectivity and structural novelty. Issue 19 (1st October 2019) - Large, Jonathan M.; Birchall, Kristian; Bouloc, Nathalie S.; Merritt, Andy T.; Smiljanic-Hurley, Ela; Tsagris, Denise J.; Wheldon, Mary C.; Ansell, Keith H.; Coombs, Peter J.; Kettleborough, Catherine A.; Whalley, David; Stewart, Lindsay B.; et al.
Graphical abstract: Abstract: Focussed studies on imidazopyridine inhibitors of Plasmodium falciparum cyclic GMP-dependent protein kinase ( Pf PKG) have significantly advanced the series towards desirable in vitro property space. LLE-based approaches towards combining improvements in cell potency, key physicochemical parameters and structural novelty are described, and a structure-based design hypothesis relating to substituent regiochemistry has directed efforts towards key examples with well-balanced potency, ADME and kinase selectivity profiles.